Parental Involvement in Learning Activities Based on Independent Learning at Kurnia Playgroup - Sartika Kale; Karlian J. Bewo; Vanida Mundiarti3; Credo Gregori Betty (Early Childhood Education Development and Studies (ECEDS), 2024)
The purpose of this study is to describe specifically about the process of parental involvement in independent learning-based learning activities. Located in the Kurnia Playgroup, this study involved three parents as the main informant and one teacher as a supporting informant. Data collection using interview techniques carried out for three days and checking the validity of data using source triangulation techniques. After the data is collected, it is coded and five themes are assigned. The results obtained are forms of involvement such as guidance in doing tasks at home, intracurricular activities at school and extracurricular; parents are involved when teachers are on duty outside of school or out of town, during long holidays, at the beginning, middle and end of the semester, and are involved two or three times a week; the parties involved are mother, father and grandmother; Obstacles in parental involvement are children who are less enthusiastic or children's abilities are less prominent when guided by parents; and parents feel happy and trusted when involved.